2016
DOI: 10.1111/trf.13869
|View full text |Cite
|
Sign up to set email alerts
|

Functional antibodies to Haemophilus influenzae type B, Neisseria meningitidis, and Streptococcus pneumoniae contained in intravenous immunoglobulin products

Abstract: Most of the tested commercial IVIG products had sufficient functional antibodies against Hib, pneumococcus, and meningococcus to protect patients with PAD receiving IVIG treatment. Regular and continuous evaluation of IVIG products is necessary to maintain an optimal therapeutic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 33 publications
(45 reference statements)
0
21
0
Order By: Relevance
“…Of note, anti‐TNF therapies are associated with an increased risk of tuberculosis—consistent with the idea that inhibition of MAIT cell activation by anti‐TNF therapies might contribute to this process . Finally, most of the commercial intravenous immunoglobulin G products, used for example in patients with primary antibody deficiency, contain specific antibodies against a range of pathogens . Thus, an IgG‐mediated enhancement of MAIT cell function might also be included in the mode of action of intravenous immunoglobulin G therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, anti‐TNF therapies are associated with an increased risk of tuberculosis—consistent with the idea that inhibition of MAIT cell activation by anti‐TNF therapies might contribute to this process . Finally, most of the commercial intravenous immunoglobulin G products, used for example in patients with primary antibody deficiency, contain specific antibodies against a range of pathogens . Thus, an IgG‐mediated enhancement of MAIT cell function might also be included in the mode of action of intravenous immunoglobulin G therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, studies using OPA demonstrated trends that were similar to those of studies of pneumococcal antibody levels, with findings of low lot‐to‐lot variability from individual manufacturers and significant variability in opsonic activity among the products of different manufacturers …”
Section: Pneumococcal Antibodies In Immunoglobulin Productsmentioning
confidence: 99%
“…Table presents data on antibodies to bacterial antigens from several studies of multiple lots of products produced in the US, UK, and EU . Antibodies against tetanus and diphtheria toxins are in the same range in 3 of the 4 studies which report them, but the results reported by Wu et al for products made from US source plasma seem to represent outliers, perhaps due to technical differences in the way the ELISAs were performed in that laboratory.…”
Section: Antibodies Against Common Bacterial Pathogens and Toxinsmentioning
confidence: 99%
“…In separate studies, Lee et al examined specific antibodies against H.influenzae polysaccharides in multiple lots of two Korean products . The mean contents of specific antibodies against H. influenzae polyribosyl‐phosphate, 0.29 and 0.27 μg/mg total IgG for the different products, are in good agreement with the data for Western products.…”
Section: Antibodies Against Common Bacterial Pathogens and Toxinsmentioning
confidence: 99%
See 1 more Smart Citation